2018
DOI: 10.1021/acs.jpcc.7b10607
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Host–Guest Interactions of Perylene–Diimide Dyes in Zeolite L Nanochannels

Abstract: Confinement-driven self-assembly of dyes in nanomatrices is an effective route for the production of hybrid supramolecular structures of high technological relevance, among which the archetypal zeolite L based systems are exploited in Forster resonance energy transfer (FRET) sensitized solar cells, luminescent solar concentrators, and color-changing media but also in sensing in analytical chemistry, biology, and diagnostics. Despite this progress in applications, the organization of confined chromophores in ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 142 publications
0
27
1
Order By: Relevance
“…Though the composites are technically suitable for use in solar cells and sensing applications (Section 7), acidity inside the zeolite L channel is still a limiting factor towards attaining maximum concentration of donor molecules inside the host . Nevertheless, these composites have proven to be thermally robust, and mechanically resilient up to GPa pressures; in addition, the host matrix is easy to synthesize in form of disc‐shaped crystals, for which a uniform filling of dye molecules along the channels can be accomplished . Also, the use of nanosized zeolite L crystals could further improve the luminescence properties of these hybrid materials, disclosing potential medical applications as theranostic agents …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Though the composites are technically suitable for use in solar cells and sensing applications (Section 7), acidity inside the zeolite L channel is still a limiting factor towards attaining maximum concentration of donor molecules inside the host . Nevertheless, these composites have proven to be thermally robust, and mechanically resilient up to GPa pressures; in addition, the host matrix is easy to synthesize in form of disc‐shaped crystals, for which a uniform filling of dye molecules along the channels can be accomplished . Also, the use of nanosized zeolite L crystals could further improve the luminescence properties of these hybrid materials, disclosing potential medical applications as theranostic agents …”
Section: Discussionmentioning
confidence: 99%
“…Also the dye carbonyl groups are crucial, as shown by a recent study . Indeed, X‐ray diffraction, total scattering, IR and UV‐vis data combined with modeling revealed that the perylene dye tb‐DXP is asymmetrically positioned in the channels in order to optimize, compatibly with the steric constraints, the stabilizing interactions between its carbonyl groups and the zeolite potassium cations . The relevance of the C=O⋅⋅⋅ K + interaction (amounting to ∼26 kcal/mol for perylene‐diimide) can be better understood by considering a carbonyl dye of smaller size: fluorenone.…”
Section: Organization Of Complex Species In 1dmentioning
confidence: 99%
See 2 more Smart Citations
“…The nanometric-scale geometry of zeolite pore systems allows the intensive use of zeolites in several fields such as in molecular separation processes and in heterogeneous catalysis [3,4]. Such ongoing progress in applications has been accompanied, in the latest years, by a deeper molecular-level understanding of the confined photoactive assemblies, which has been achieved through computational modelling [44][45][46][47][48][49][50], often combined with multi-technique experimental analyses [45,[50][51][52][53][54][55][56][57]. The key role of water in tuning the organization of the confined chromophores has been revealed [45,46,58], as well as the stabilizing effect of potassium cations in composites with carbonyl dyes [44,57,59].…”
Section: Introductionmentioning
confidence: 99%